Affectionate Communication Is Associated With Emotional and Relational Resources in the Grandparent-Grandchild Relationship. Issue 2 (3rd April 2017) - Mansson, Daniel Hans; Floyd, Kory; Soliz, Jordan
ABSTRACT: Grounded in affection exchange theory (AET; Floyd, 2006), this study examined the extent to which affection received from grandparents is associated with grandchildren's perceptions of their grandparents and their grandparent-grandchild relationship (in the form of emotional closeness, shared family identity, and perceived availability of social support). Young adult grandchildren ( N  = 171) completed several instruments in reference to their relationship with a specific grandparent. The results of multiple regression analyses generally supported the hypotheses that received affection is associated positively with grandchildren's perceptions of their grandparents and their grandparent-grandchild relationship. These findings support AET's utility in the grandparent-grandchild relationship and the notion that grandparents often influence their grandchildren's perceptions of their family.